2016
DOI: 10.2486/indhealth.2015-0217
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-reported driver sleepiness and incidents in city bus drivers

Abstract: Driver fatigue has received increased attention during recent years and is now considered to be a major contributor to approximately 15–30% of all crashes. However, little is known about fatigue in city bus drivers. It is hypothesized that city bus drivers suffer from sleepiness, which is due to a combination of working conditions, lack of health and reduced sleep quantity and quality. The overall aim with the current study is to investigate if severe driver sleepiness, as indicated by subjective reports of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 46 publications
3
38
2
1
Order By: Relevance
“…23 In a similar study, Anund et al found that 19% of bus drivers in Sweden experienced severe sleepiness, to the point that the affected individual had to fight to stay awake while driving at least two or three times per week. 24 The BQ is a useful tool to screen for OSAS and has been used in previous epidemiological research targeting the Omani population. 20 Young et al previously demonstrated that individuals with OSAS are at greater risk of having car crashes due to the symptoms of daytime sleepiness associated with the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a similar study, Anund et al found that 19% of bus drivers in Sweden experienced severe sleepiness, to the point that the affected individual had to fight to stay awake while driving at least two or three times per week. 24 The BQ is a useful tool to screen for OSAS and has been used in previous epidemiological research targeting the Omani population. 20 Young et al previously demonstrated that individuals with OSAS are at greater risk of having car crashes due to the symptoms of daytime sleepiness associated with the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…4 Driver fatigue is now considered to be a major contributor to 15-30% of all crashes. [4][5][6][7][8] Inappropriate driving behaviour (DB) (eg, speeding) is often dealt with by sanctions and/or by attendance at appropriate training courses. 9 A major problem with much of the research is that factors are often studied in isolation whereas it is clear that a multivariate approach is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Las características sociodemográficas de los participantes de los diversos estudios relacionados con la presente investigación no pueden ser contrastadas, debido a que cada una de las características poblacionales en análisis son propias, solo se mencionarán las características más resaltantes halladas en cada uno de los estudios, por ejemplo, los estudios de Anund et al (20) , Muñoz Escobar (17) , Deza et al (14) , Intriago Alvarez (19) y Suarez Molina (15) concuerdan en que la mayoría de los conductores que participaron en cada uno de los estudios presentaban sobrepeso u obesidad. Al respecto, se puede mencionar que estos problemas nutricionales, podría deberse al sedentarismo que los conductores experimentan durante toda su actividad laboral, sin opción de realizar algún tipo de ejercicio físico, puesto que esta actividad demanda de una gran concentración por parte del conductor.…”
Section: Discussionunclassified